2022
DOI: 10.1186/s40323-022-00234-8
|View full text |Cite
|
Sign up to set email alerts
|

Empowering engineering with data, machine learning and artificial intelligence: a short introductive review

Abstract: Simulation-based engineering has been a major protagonist of the technology of the last century. However, models based on well established physics fail sometimes to describe the observed reality. They often exhibit noticeable differences between physics-based model predictions and measurements. This difference is due to several reasons: practical (uncertainty and variability of the parameters involved in the models) and epistemic (the models themselves are in many cases a crude approximation of a rich reality)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 131 publications
0
6
0
Order By: Relevance
“…It is here that artificial intelligence and machine learning methods come into play [14]. In order to speed-up optimal decisions, reinforcement learning is increasingly considered, as commented before, in particular for autonomous system applications [9].…”
Section: Researchmentioning
confidence: 99%
“…It is here that artificial intelligence and machine learning methods come into play [14]. In order to speed-up optimal decisions, reinforcement learning is increasingly considered, as commented before, in particular for autonomous system applications [9].…”
Section: Researchmentioning
confidence: 99%
“…Multiple novel applications are appearing on a daily basis. A combination of data-driven modeling and the more experienced physics-based modeling, to enhance diagnosis and prognosis, taking the best of both paradigms, is also an active research topic [1]. Multiple data-driven approaches, combined with physical modeling, are used and referred to as hybrid models [2].…”
Section: Introduction and Related Workmentioning
confidence: 99%
“…This work primarily focuses on snapshots-based reduced-order modeling (a subject that is extensively discussed in [2] ) and, particularly, on the Proper Orthogonal Decomposition —POD— and on the sparse Proper Generalized Decomposition —sPGD—. Extensive reviews and investigations on such techniques can be found in [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] . In particular, in the recent work [10] , the authors deal with parametric metamodeling of curves, based on POD, PGD, data alignment, data clustering and data classification, with emphasis in computational materials science.…”
Section: Introductionmentioning
confidence: 99%